THE FREQUENCY OF COMPOUND CHONDRULES AND IMPLICATIONS FOR CHONDRULE FORMATION - Ciesla F.J.; Lauretta D.S.; Hood L.L. (My University, 2004)
The properties of compound chondrules and the implications that they have for the conditions and environment in which chondrules formed are investigated. Formulae to calculate the probability of detecting compound chondrules in thin sections are derived and applied to previous studies. This reinterpretation suggests that at least 5% of chondrules are compounds, a value that agrees well with studies in which whole chondrules were removed from meteorites. The observation that adhering compounds tend to have small contact arcs is strengthened by application of these formulae. While it has been observed that the secondaries of compound chondrules are usually smaller than their primaries, these same formulae suggest that this could be an observation bias. It is more likely than not that thin section analyses will identify compounds with secondaries that are smaller than their primaries. A new model for chondrule collisional evolution is also developed. From this model, it is inferred that chondrules would have formed, on average, in areas of the solar nebula that had solids concentrated at least 45 times over the canonical solar value.